A novel analytical model for wind field simulation under typhoon boundary layer considering multi-field correlation and height-dependency. Issue 175 (April 2018) - Fang, Genshen; Zhao, Lin; Cao, Shuyang; Ge, Yaojun; Pang, Weichiang
Abstract: On the basis of the measured atmospheric pressure distribution rule fitted by on-the-spot near-ground observation data, the typhoon's height-dependent pressure field was developed with the aid of gas state and hydrostatic balance equations. Probabilistic correlation among mesoscale typhoon field parameters was taken into account. A reduced calculation pattern was proposed by carrying out the scale analysis of three dimensional Navier-Stokes equations to solve the wind velocity field in the typhoon boundary layer. A novel typhoon velocity field model suitable for the gradient layer and boundary layer was then established considering the multi-field parameters correlation and terrain effects. The influence of height-dependent eddy viscosity, which was also closely related to the pressure field and terrain type, on the wind speed profiles under the typhoon boundary layer was considered and discussed. An improved iterative loop algorithm introducing the spatial distribution of eddy viscosity at the low-level boundary layer along the vertical and radial directions was utilized. Furtherly, case studies of the specific typhoon wind field was re-illustrated and compared with the observed wind speed profiles averaged from upper-level dropsondes data and low-level profiles measured by meteorological towers. Three typical regions of vertical wind speed profiles were summarized. Wind speed time series observed by meteorological stations and sea surface wind field snapshots of several typhoons obtained from Hurricane Research Division of National Oceanic and Atmospheric Administration American (H*Wind) were also compared. In general, some specific wind environment characteristics such as non-exponential wind profiles in typhoon boundary layers can be re-illustrated with satisfactory precision by these improved algorithms. Highlights: A novel analytical typhoon boundary layer model considering multi-field correlation and height-dependency was developed. The height-dependent feature of a typhoon pressure field cannot be neglected which determines the distribution of wind speed field. An alternative and simplified approach to model the spatial variation of eddy viscosity in the Prandtl layer was proposed. Three regions for typhoon vertical profiles, boundary layer decay, supergradient and gradient decay regions, were classified. Multiple verifications by observation data was conducted to demonstrate the accuracy of present model.